Developing Teaching Materials â€œIPAS Flipbookâ€ for Elementary Schools - Atik Puspita Rini; Retno Danu Rusmawati; Rufiâ€™i Rufiâ€™i (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
The flipbook media science teaching materials were developed because in the schools where the research was carried out, especially in the UPT SDN 236 Gresik and also in the school cluster area of Menganti District, Gresik Regency, this type of media has never been developed. Learning resource media are mostly in the form of printed books and pdf format books. The content of the material is developed and adjusted contextually. With the existence of new learning resources, it is hoped that students will be interested, so that they are more intensive in studying the material of IPAS CHAPTER VI and subsequently it is expected to have an impact on increasing learning outcomes. The development research model used is Borg and Gall with 10 development steps to the dissemination and implementation stages. The flipbook making application program used is flip pdf professional. The data collection technique uses observation, interviews, and filling in instruments carried out by three experts, namely design experts, material experts, and media experts. Instruments are also filled by students after small tests, medium group tests, and field tests. The results of data processing by media experts are 85%, material experts are 98%, design experts are 92%, from students are 87%, and from peers are 95%, which are interpreted based on the Likert scale is included in the category of feasible and qualified for use.Keywords: Teaching materieals, flipbook, elementary school.Â